The Effect of Digital Content on Listenig Skills in Middle School Turkish Teaching - Özcan, Muhammed; Yavuz, Serdar (Asya Publishing and Consultancy, 2024)
The course of development of technology, its speed in the recent period and the point it has reached have led our relationship with technology to become a necessity rather than a choice. In this respect, teaching activities that are not intertwined with technology and do not include digital elements will remain as practices that will not go beyond the interest and expectations of students who are the subject of educational environments. This study, which examines the effect of digital content on listening skill in secondary school Turkish teaching, is at an important point in terms of showing the effect of digital elements on listening skill, which is the first learning channel of human beings and will continue until death, and which should be carefully emphasized in terms of forming the basis for other language skills. The sample of this study consists of 60 students in the seventh grade of a secondary school in Elazığ province. In the study, mixed research method was preferred as the method and sequential explanatory design was preferred as the design. Quasi-experimental design was used in the quantitative part of the study and phenomenology design was used in the qualitative part. In the quantitative part of the study, there was one control and one experime ntal group. In order to obtain quantitative data within the scope of the research, the Listening Skills Scale developed by Yalçın & Özcan (2022) was applied to the control and experimental groups as pre-test and post-test. The experimental and control groups were determined according to the pre-test results of the students participating in the study. In the qualitative part of the study, data were obtained from interviews with the students and these interviews were analyzed by content analysis. The results of the study showed that there was a significant difference between the listening skill scale scores of the students in the experimental and control groups in the post-test application in favor of the experimental group, there was a significant increase between the pre-test and post-test scores of the listening skill scale applied to the control group, and there was a significant difference between the pre and post-application listening skill scale scores of the experimental group. Considering the results obtained from the interviews, it was seen that listening practices enriched with digital content facilitated comprehension, digital content practices improved listening skills and created a desire to participate in new activities. At the end of the study, s uggestions were made for researchers, educators and related institutions. © 2024, Asya Publishing and Consultancy. All rights reserved.
Keywords: Digital content; Listening activities; Listening skills; Middle school students; Multimedia